The Behavior of Gypseous Soil under Vertical Vibration Loading (Journal of Engineering, 2014)
The dynamic response of foundation rest on collapsible soil in dry and soaked states is studied through wide experimental programmed. Gypseous soil from Tikrit governorate area was obtained and subjected to various physical and chemical analysis to determine its properties. Steel rectangular footing (400x200x20) mm is manufactured. The machine is fitted to the footing, then the model machine foundation is placed centrally over the prepared soil layer in steel container (1200x 1000x1000)mm with proper care to maintain the center of gravity of whole system lie in the same vertical line with container.Then, the footing is subjected to vertical harmonic loading using a rotating mass type mechanical oscillator to simulate different dynamic loads. The effect of soaking and eccentric mass was investigated. The results showed that the amplitude of displacement in dry state is greater than its value at soaked state, while the resonant frequency in the soaked state is greater than in dry state. Also, the results showed that for specific frequency ,an increasing in eccentric mass leads to increase in amplitude of displacement. Moreover, an increasing in resonant frequency can be absoreved when eccentric mass is increased.